2017
DOI: 10.1111/apm.12728
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronate effect on bacterial biofilm in ENT district infections: a review

Abstract: Bacterial resistance is a growing phenomenon which led the scientific community to search for new therapeutic targets, such as biofilm. A bacterial biofilm is a surface-associated agglomerate of microorganisms embedded in a self-produced extracellular polymeric matrix made of polysaccharides, nucleic acids, and proteins. Scientific literature offers several reports on a biofilm's role in infections regarding various body districts. The presence of a bacterial biofilm is responsible for poor efficacy of antibio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Its presence in bacterial biofilm (BBF) is related to the severe clinical situation of CRS. Some studies have reported the anti-BBF effects of HA in vivo, especially in the form of atomized sodium hyaluronate plus normal saline [59]. Cassandro et al [60] divided 80 patients with CRS and nasal polyposis without FESS into 4 groups.…”
Section: Hyaluronic Acidmentioning
confidence: 99%
“…Its presence in bacterial biofilm (BBF) is related to the severe clinical situation of CRS. Some studies have reported the anti-BBF effects of HA in vivo, especially in the form of atomized sodium hyaluronate plus normal saline [59]. Cassandro et al [60] divided 80 patients with CRS and nasal polyposis without FESS into 4 groups.…”
Section: Hyaluronic Acidmentioning
confidence: 99%
“…In this experimental study, HA was shown to be able to reduce bacterial adhesion to a cellular substrate in a concentration-dependent manner. The antibiofilm action, exerted by HA in ear, nose and throat districts, has been recently reviewed [31]. The authors conclude that "its efficacy in treating rhinosinusitis, whether or not associated with polyposis, is well documented, as well as results from its effects on mucociliary clearance, free radical production and mucosal repair."…”
Section: Antiadhesive and Antibiofilm Properties Of Hamentioning
confidence: 99%
“…Another product is Hyaluronic Acid. Use of protease products such as papain and bromelain are of value in delivering antibiotics into the biofilm [13].…”
Section: Viscosity Therapymentioning
confidence: 99%